Kawasan Heritage Gajah Mada di Kota Denpasar sebagai Destinasi Wisata Alternatif - I Kadek Pande Maha Dwija; Nyoman Diah Utari Dewi; Luh Riniti (Penerbit Goodwood, 2023)
Purpose: The aim is to make the Denpasar Gajah Mada Area an alternative tourist destination regarding history, culture and business that highlights aspects of the building's heritage for tourists in addition to other tours in Denpasar City. In the 80s, the Jalan Gajah Mada area in Denpasar was synonymous with the hangouts of the capital's youth, especially the generation that grew up in the 70-80s. This area has a backdrop of old buildings that function as shops. With a situation where changes in form, structure, function transfer and lack of utilization of old buildings along the Gajah Mada area have resulted in the loss and erosion of the Gajah Mada Heritage area, protection, utilization and development are needed as an alternative tourist destination in Denpasar City apart from natural tourism. Methodology: This research is a qualitative research located in Jalan Gajah Mada, Denpasar, using observation and documentation data collection methods. The Gajah Mada Denpasar area is located around Jalan Gajah Mada, Jalan Kartini to Jalan Veterans. Result: The research provides a SWOT analysis to stakeholders regarding the protection and utilization as a tourist destination for both the Regional Government, Cultural Observers and local Business Actors as well as making the Gajah Mada Area an alternative tourist destination.